Analysis of Characters and Characteristics in The Novel "Perempuan di Titik Nol" By Nawal El Saadawi Using A Feminism Approach - Narimawati, Umi; Nurhayatin, Titin; Fitriani, Rani Siti (Jurnal Pendidikan Bahasa dan Sastra, 2023)
This article analyzes the characters and characterization in the novel "Women at Zero Point" by Nawal El Saadawi using a feminist approach. This novel depicts women's struggle in facing oppression, violence and gender injustice in a patriarchal society. A feminist approach is used to analyze how the female characters in this novel face these problems and struggle to find freedom. This analysis uses a literature review method by referring to the novel "Perempuan di Titik Zero" and relevant feminist literature studies. Focus is given to the main character, Firdaus, as well as other female characters in this novel. The results of the analysis show that the female characters in this novel face oppression and violence carried out by the patriarchal system. Firdaus, as the main character, faces various forms of sexual exploitation, domestic violence, and objectification by the surrounding community. However, this novel also highlights women's solidarity as a source of strength and support in their struggle against gender injustice. A feminist approach helps in seeing how the author criticizes patriarchal norms that limit women. Firdaus and other female characters challenge narrow social expectations and attempt to shape their identities outside these constraints. In conclusion, This analysis confirms that the novel "Women at Point Zero" is a reflection of women's struggle to seek freedom and overcome gender injustice in a patriarchal society. Women's solidarity and criticism of patriarchal norms are important themes in this novel, inviting readers to consider the role and influence of patriarchy in women's lives.